Towards a Stunting-Free Gunungsitoli City: Policy Evaluation and Challenges of the Economic Approach - Eldad Chalis Natha Nias Ndruru; Asep Sumaryana; Heru Nurasa (Universitas KH. Abdul Chalim Mojokerto, 2025)
The purpose of this study is to evaluate policies to accelerate stunting reduction and the challenges of economic approaches. Policy evaluation is an important basis for seeing and assessing a policy or program, namely the policy of accelerating stunting reduction in Gunungsitoli City. This study uses a qualitative method with a case study approach. Data was collected through interviews, literature reviews, and observations. Interviews are conducted by informants, and then the data is processed, and qualitative data analysis is carried out. Based on the results of the research using evaluation indicators that believe in effectiveness, efficiency, adequacy, leveling, responsiveness, and accuracy, the implementation has not been optimal or running well based on several criteria, namely the budget from the APBD for policies and programs to accelerate stunting reduction is still limited, access to stunting sufferers is still constrained considering the demographic conditions of the region spread across various regions, the existence of complex socialization So that the delivery of information is not effective and the implementation time of policies and programs is not too much so that the implementation of policies does not run well and the short implementation time makes programs and policies not optimal in terms of their implementation and economic challenges in handling stunting are met with poverty and limited access to nutrition, dependence on external resources, and economic impacts do not last long This stunting results in a decrease in productivity labor force, the burden of regional health increased, and poverty arose.